Genetic Basis of Antigenic Variation of SAT3 Foot-And-Mouth Disease Viruses in Southern Africa - Maake, Lorens; Harvey, William T.; Rotherham, Lia; Opperman, Pamela; Theron, Jacques; Reeve, Richard; Maree, Francois F. (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) continues to be a major burden for livestock owners in endemic countries and a threat to FMD-free countries. The epidemiology and control of FMD in Africa is complicated by the presence of five clinically indistinguishable serotypes. Of these the Southern African Territory (SAT) type 3 has received limited attention, likely due to its restricted distribution and it being less frequently detected. We investigated the intratypic genetic variation of the capsid-coding region of 22 SAT3 viruses and confirmed the geographical distribution of four topotypes. The antigenic cross-reactivity of 12 SAT3 viruses against reference antisera was assessed by performing virus neutralization assays and calculating the r1-values, which is a ratio of the heterologous neutralizing titre to the homologous neutralizing titre. Interestingly, cross-reactivity between the SAT3 reference antisera and many SAT3 viruses was notably high (r1-values > 0.3). Moreover, some of the SAT3 viruses reacted more strongly to the reference sera compared to the homologous virus (r1-values > 1). An increase in the avidity of the reference antisera to the heterologous viruses could explain some of the higher neutralization titres observed. Subsequently, we used the antigenic variability data and corresponding genetic and structural data to predict naturally occurring amino acid positions that correlate with antigenic changes. We identified four unique residues associated with a change in cross-reactivity, with two sites that change simultaneously. The analysis of antigenic differences is critical for surveillance and proper vaccine selection for effective control or the design of vaccine antigens tailored for specific geographic localities, using reverse genetics.